A hybrid digital watermarking algorithm - Sabinus D'Costa (2023)
Watermarking or data hiding is the process of embedding data into a multimedia element such as image, audio or video. This embedded data can later be extracted from, or detected in, the multimedia for security purposes. A watermarking algorithm consists of the watermark structure, an embedding algorithm and an extraction, or detection, algorithm.